2014
DOI: 10.1542/peds.2013-0958
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Parental Protection of Children From Tobacco Smoke Exposure

Abstract: BACKGROUND AND OBJECTIVE: Worldwide, roughly 40% of children are exposed to the damaging and sometimes deadly effects of tobacco smoke. Interventions aimed at reducing child tobacco smoke exposure (TSE) have shown mixed results. The objective of this study was to perform a systematic review and meta-analysis to quantify effects of interventions aimed at decreasing child TSE.METHODS: Data sources included Medline, PubMed, Web of Science, PsycNet, and Embase. Controlled trials that included parents of young chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 95 publications
(305 reference statements)
4
64
2
2
Order By: Relevance
“…A c c e p t e d M a n u s c r i p t 13 Although most of the parents interviewed in this study believed that biochemical feedback could spur them to change their behaviors, intervention trials reported in the literature found that interventions using biochemical feedback exhibited only a very small benefit [44]. This finding is unsurprising given the notorious gap between intent to change behavior and actual behavior change (as assessed by intervention trials) [46,47].…”
Section: Page 13 Of 25mentioning
confidence: 76%
See 1 more Smart Citation
“…A c c e p t e d M a n u s c r i p t 13 Although most of the parents interviewed in this study believed that biochemical feedback could spur them to change their behaviors, intervention trials reported in the literature found that interventions using biochemical feedback exhibited only a very small benefit [44]. This finding is unsurprising given the notorious gap between intent to change behavior and actual behavior change (as assessed by intervention trials) [46,47].…”
Section: Page 13 Of 25mentioning
confidence: 76%
“…Some investigators used biochemical feedback in the context of interventions to help parents reduce exposure to tobacco smoke. Four trials [22,24,42,43] included in a recent meta-analysis [44] assessed the effect of biochemical feedback on exposure levels or protection behaviors. Individually, none of these trials showed a statistically significant effect, while a synthesis of all four trials showed a small advantage in the intervention groups (RR=1.14 [1.03,1.28], p=.02).…”
Section: Use Of Biomarkers For Motivating Behavior Changementioning
confidence: 99%
“…Children can be protected from smoking initiation and smoking exposure if their parents quit smoking [19]. This study aims to determine smoking family members at home to successful smoking cessation in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] The consequences are given by the susceptibility of children to smoke toxicity and include a higher risk for sudden infant death, middle ear pathology, severe asthma, acute respiratory infection, pneumonia, and impaired lung function, as well as school absenteeism and restricted activities. 7,8 T h e r e f o r e , t h e d i f f e r e n t governments have implemented policies and interventions aimed at reducing home exposure through education campaigns for parents and at avoiding the exposure of children in public places. 9 This was evidenced in Chile by the implementation of the anti-smoking law (19419 and 20660).…”
Section: Introductionmentioning
confidence: 99%